Man and Environment - the Nigerian Situation - Imevbore, A.M.A (Obafemi Awolowo University Press, 2013)
MAN is an organism and his environment includes all things, living and non-living, which influence his life The study of man's relationship with his environment dates back to the time of his emergence as the dominant species on earth. In the beginning was the land, the plants and the animals. Plants and animals respond to the forces of nature and this involves interaction with the environment. During such interaction animals alter their behavior to adapt to changing conditions, but this rarely causes trouble. If they are unable to change, they simply die out, and become extinct. More often than not it is only man that upsets the delicate balances of nature, creating environmental problems. This trouble would of course be overcome if man became extinct. However, this is not a solution I would wish to advocate.